Frontal surface area measurements in national caliber swimmers - Cappaert, J. M.; Gordon, B. J.; Frisbie, K. (Medicine & Science in Sports & Exercise, 1997)
Frontal surface area during crawl stroke was measured and compared to methods which estimate frontal surface area. National caliber crawl stroke swimmers (N = 10) swam a maximal 50 m sprint. Frontal surface area for one complete stroke cycle was digitized by assessing the trunk only, and the body (arms, trunk, legs). Frontal surface was also calculated using the methods of Clarys (1979), Yeadon (torso calculation, 1990), and Kolmogorov and Duplishcheva (1992). All methods produced significantly different results except for the digitized trunk area and Clary's method as well as trunk and Yeadon's method. Implication: Estimating frontal surface area is not an accurate procedure. Caution should be exercised in calculations for active or passive drag in swimming when frontal surface area needs to be considered. Unless digitized values can be obtained, calculations should not be entertained.